1985
DOI: 10.1126/science.2983431
|View full text |Cite
|
Sign up to set email alerts
|

A Region of the Herpesvirus saimiri Genome Required for Oncogenicity

Abstract: Herpesvirus saimiri naturally infects squirrel monkeys (Saimiri sciureus) without producing signs of disease; infection of other New World primates, however, results in a rapidly progressing, malignant, T-cell lymphoma. Results described in this report identify a region of the viral genome that is required for oncogenicity in owl monkeys (Aotus trivirgatus); this region is not required for replication of the virus. This is believed to be the first such genomic region identified in a herpesvirus system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 7 publications
5
91
1
Order By: Relevance
“…Our RT-PCR analysis demonstrated that the ORF5 genes of both viruses are spliced near the 5Ј end of the coding sequence, which leads to the addition of 14 identical amino acids to their amino terminus, providing the amino-terminal myristoylation site for membrane attachment. Sequence comparison of 13 ORF5 alleles showed that ORF5 was relatively conserved within each subgroup but showed a dramatic sequence divergence between subgroups; for example, there was 97 to 100% identity among members of the A11 cluster of subgroup A but only 46 to 50% identity between the A11 cluster and subgroup C. Among more than 80 different open reading frames compared between HVS subgroup A11 and C488 strains, only two other open reading frames have been shown to display considerable sequence divergence (2,14,36). These are the STP oncoprotein and the Tip signaling protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our RT-PCR analysis demonstrated that the ORF5 genes of both viruses are spliced near the 5Ј end of the coding sequence, which leads to the addition of 14 identical amino acids to their amino terminus, providing the amino-terminal myristoylation site for membrane attachment. Sequence comparison of 13 ORF5 alleles showed that ORF5 was relatively conserved within each subgroup but showed a dramatic sequence divergence between subgroups; for example, there was 97 to 100% identity among members of the A11 cluster of subgroup A but only 46 to 50% identity between the A11 cluster and subgroup C. Among more than 80 different open reading frames compared between HVS subgroup A11 and C488 strains, only two other open reading frames have been shown to display considerable sequence divergence (2,14,36). These are the STP oncoprotein and the Tip signaling protein.…”
Section: Discussionmentioning
confidence: 99%
“…HVS infection is endemic and nonpathogenic in its natural host, squirrel monkeys (Saimiri sciureus) (15). However, HVS infection of other species of New World primates results in rapidly progressing fatal T-cell lymphomas and leukemias (14,29). Besides its potent oncogenicity in vivo, HVS can immortalize peripheral blood mononuclear cells of human, rhesus monkey, and common marmoset to IL-2-independent growth in vitro (2,5).…”
mentioning
confidence: 99%
“…HVS can be further sub-classified into three subgroups (A, B, and C) on the basis of the extent of DNA sequence divergence at the left end of L-DNA. Mutational analysis on the gene products in this region, designated with saimiri transforming protein (STP-A, or C) has revealed that STP is not required for viral replication but for immortalization (Desrosiers et al, 1984;1985). Previous studies have reported that STP-A11 interacts with Src at the residue of 115YAEV118 (Lee et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although it does not cause any disease in its natural host, infection in other New World primates such as tamarins, common marmosets, and owl monkey causes acute peripheral T cell lymphoma within less than 2 months (23,24). In addition, the virus is also capable of transforming simian and human T cells in vitro (25,26).…”
mentioning
confidence: 99%